Peran Kepuasan Kerja Terhadap Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Perusahaan Manufaktur - Nancy Yusnita; Nurul Sahda, Naflah; Totok Irawan, Towaf (International Journal Administration, Business & Organization, 2023)
The purpose of this study is to provide recommendations for companies to improve the performance of their employees by analyzing the relationship between the variables in this study, namely work environment and job satisfaction with performance. This research was conducted at PT. Faco Global Engineering is a steel fabrication company that will continue to support the needs of steel construction manufacturing and engineering services. This research is quantitative research with a survey approach. The number of samples used in the study was 81 people who were employees of PT Faco Global Engineering. The method for processing and analyzing data uses Partial Least Square (PLS) with SmartPLS software. The results of the study show that there is a positive and significant direct effect of the work environment on employee performance. There is a positive and significant direct effect of job satisfaction on employee performance. There is a positive and significant direct effect of the work environment on job satisfaction. There is a positive and significant indirect effect of the work environment on employee performance. Through job satisfaction. This study shows the effective role of the intervening variable, namely job satisfaction.